ANALISIS RELEVANSI NILAI VARIABEL FUNDAMENTAL PADA PERUSAHAAN E&P MIGAS DI KAWASAN ASIA - , RADITYA HARI SAKSANA, Fuâad Rakhman, M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to examine the value-relevance of a group of upstream oil and gas industryâs fundamental variables to the market value of equity. The fundamental variables are used by oil and gas industry analyst in evaluating the performance of upstream company. Furthermore, this study also provides the evidence that the fundamental variables are incrementally value-relevant over the accounting earnings and the book value of equity. Sample consists of 20 firms listed in Asian regional stock exchanges (Singapore, Indonesia, Thailand, India, Hong Kong, and Japan) for the year of 2003 â 2012. The result of this study shows that several fundamental variables have a significant relationship with the market value of equity. In addition, this paper also captures that a group of fundamental variables are incrementally value-relevant over the accounting earnings and the book value of equity even after controlling for difference in accounting method and in accounting standard that used by upstream companies. Therefore we can conclude that the fundamental variables can be an instrument in predicting the value of equity at upstream oil and gas industry.